Lactobacillus reuteri in digestive system diseases: focus on clinical trials and mechanisms - Peng, Yijing; Ma, Yizhe; Luo, Zichen; Jiang, Yifan; Xu, Zhimin; Yu, Renqiang (Frontiers in Cellular and Infection Microbiology, 2023)
Objectives: Digestive system diseases have evolved into a growing global burden without sufficient therapeutic measures. Lactobacillus reuteri (L. reuteri) is considered as a new potential economical therapy for its probiotic effects in the gastrointestinal system. We have provided an overview of the researches supporting various L. reuteri strains' application in treating common digestive system diseases, including infantile colic, diarrhea, constipation, functional abdominal pain, Helicobacter pylori infection, inflammatory bowel disease, diverticulitis, colorectal 2 cancer and liver diseases.The summarized literature in this review was derived from databases including PubMed, Web of Science, and Google Scholar.The therapeutic effects of L. reuteri in digestive system diseases may depend on various direct and indirect mechanisms, including metabolite production as well as modulation of the intestinal microbiome, preservation of the gut barrier function, and regulation of the host immune system. These actions are largely strain-specific and depend on the activation or inhibition of various certain signal pathways. It is well evidenced that L. reuteri can be effective both as a prophylactic measure and as a preferred therapy for infantile colic, and it can also be recommended as an adjuvant strategy to diarrhea, constipation, Helicobacter pylori infection in therapeutic settings.While preclinical studies have shown the probiotic potential of L. reuteri in the management of functional abdominal pain, inflammatory bowel disease, diverticulitis, colorectal cancer and liver diseases, its application in these disease settings still needs further study.This review focuses on the probiotic effects of L. reuteri on gut homeostasis via certain signaling pathways, and emphasizes the importance of these probiotics as a prospective treatment against several digestive system diseases.